Surface-Level Analysis ofInternationalEconomic AgreementsandTheir Strangulatory Impact on Pakistan Economy (Journal of Asian Development Studies, 2024)
The international economic system that evolved after World War II, which was conceived by and rolled out on behalf of Global North states,essentially stood on a tripod of international economic agreements, that is, International Investment Agreements, Double Taxation Agreements, and International Trade Agreements. The ostensible purpose of these agreements was to (a) facilitate cross-border deployment of surplus investible capital, (b) export of finished and capital goods, and (c) allocate favorably taxing rights betweenstateson various incomes earned by multinational enterprisesin overseas jurisdictions. Intuitively, when these agreementsare signed by and between states at par level of economic development, their resultant economic outcomes would be equal or near-equal. But when such agreements are signed in asymmetrical bilateral economic settings, that is, between a developed and a developing country, the resultant economic outcomes would most likely be lopsided and inimical to the economic interests of weaker partner in the equation. From the global south perspective, these agreements expose developing countries to international arbitration on account of suits filed by investors, erode their tax base by allowingmultinational corporationsto enter aggressive tax planning ploys, and undermine their export competitiveness vis-à-vis stronger economies. The paper premises that developing countries that signed more of these agreements, would find themselves in a deeper trouble than those which signed less of them, and that countries that signed the agreements in a quicker span of time, got into trouble quicker, too. In this connection, Pakistan is brought in to undertake a surface-level time-series analysis of its signing agreements and the corresponding trajectory of select economic indicators over the past seven decades